Colloidal hydrogels made of gelatin nanoparticles exhibit fast stress relaxation at strains relevant for cell activity. (15th January 2022) - Bertsch, Pascal; Andrée, Lea; Besheli, Negar Hassani; Leeuwenburgh, Sander C.G.
Abstract: Viscoelastic properties of hydrogels such as stress relaxation or plasticity have been recognized as important mechanical cues that dictate the migration, proliferation, and differentiation of embedded cells. Stress relaxation rates in conventional hydrogels are usually much slower than cellular processes, which impedes rapid cellularization of these elastic networks. Colloidal hydrogels assembled from nanoscale building blocks may provide increased degrees of freedom in the design of viscoelastic hydrogels with accelerated stress relaxation rates due to their strain-sensitive rheology which can be tuned via interparticle interactions. Here, we investigate the stress relaxation of colloidal hydrogels from gelatin nanoparticles in comparison to physical gelatin hydrogels and explore the particle interactions that govern stress relaxation. Colloidal and physical gelatin hydrogels exhibit comparable rheology at small deformations, but colloidal hydrogels fluidize beyond a critical strain while physical gels remain primarily elastic independent of strain. This fluidization facilitates fast exponential stress relaxation in colloidal gels at strain levels that correspond to strains exerted by cells embedded in physiological extracellular matrices (10-50%). Increased attractive particle interactions result in a higher critical strain and slower stress relaxation in colloidal gels. In physical gels, stress relaxation is slower and mostly independent of strain. Hence, colloidal hydrogels offer the possibility to modulate viscoelasticity via interparticle interactions and obtain fast stress relaxation rates at strains relevant for cell activity. These beneficial features render colloidal hydrogels promising alternatives to conventional monolithic hydrogels for tissue engineering and regenerative medicine. Statement of significance: In the endeavor to design biomaterials that favor cell activity, research has long focused on biochemical cues. Recently, the time-, stress-, and strain-dependent mechanical properties, i.e. viscoelasticity, of biomaterials has been recognized as important factor that dictates cell fate. We herein present the viscoelastic stress relaxation of colloidal hydrogels assembled from gelatin nanoparticles, which show a strain-dependent fluidization at strains relevant for cell activity, in contrast to many commonly used monolithic hydrogels with primarily elastic behavior. Graphical abstract: Image, graphical abstract